Experimental studies of truck transport brake pads materials friction properties (Transport systems and technologies, 2023)
The work presents the results of experimental systematic studies of "wheel-brake pad" friction pairs wear resistance and the effect of the wear-resistant coating on the wear, in particular, from metal-ceramic friction materials (ФМК-8), carbon composite materials (ВВКМ) in comparison with carbon steel of grade 45. It was established that the instantaneous values of brake pads friction coefficients during the tests on inertial stand are random in nature and require the use of mathematical statistics methods for their analysis. Change nature in pads and wheels friction force instantaneous values is determined by pressing forces. It is shown that the mathematical expectation of the friction coefficients values is within the normalized permissible interval. The probability of friction coefficients instantaneous values matching into the normalized interval at a pressing force of 10kN is 0,6-0,8 for speeds up to 60 km/h, for the rest is more than 0,8 at pressing force of 20kN, the specified probability exceeds 0,85 for the entire range of speeds. With a pressing force of 20kN, the probability of values exceeding the normalized interval does not exceed 0,15, with a pressing force of 10kN, the friction coefficients exceeded the maximum normative values more than 0,35 for speeds up to 40 km/h. It has been established that the most wear-resistant pads are coated with metal-ceramic material (ФМК-8) and carbon-carbon composite materials (ВВКМ). It is shown that the described technique based on the mathematical statistic application allows to perform more in-depth analysis of freight wheeled road trains brake pads frictional properties.
Keywords: mathematical statistics, friction, destruction, friction materials, friction pairs wear resistance.